The wage effects of offshoring to the East and West: evidence from the German labor market - Konstantin Koerner (Review of World Economics, 2022)
This paper analyzes the labor market effects of offshoring in a high-wage home country and how these effects crucially depend on (1) Job complexity and (2) The characteristics of the destination country. It thereby links several sources: rich administrative data on individuals and plants in the German manufacturing industries, information on a job's task bundle, and the evolution of imported inputs from low- or high-wage destinations, which are represented by Eastern and Western Europe, respectively. Offshoring to these origins has opposing effects on German wages with respect to the relative task complexity of jobs: While offshoring to the West puts pressure on the wages of complex jobs and increases the wages of simple jobs, offshoring to the East entails the opposite effect. The overall effect adds up to a 4.2 percent increase in wages for jobs with high complexity, while low-complexity jobs see a 3.9 percent decrease in wages.
Keywords: F15; F16; J31; 330; Offshoring; Tasks; Production chains; Offshorabiliy; Wages; Globalization